Multiple low salinity stress modes provided novel insight into the metabolic response of Scylla paramamosain adapting to inland saline-alkaline water - Niu, Mingming; Gao, Gao; Qin, Kangxiang; Chen, Yuhao; Wang, Huan; Li, Xing; Liang, Guoling; Wang, Chunlin; Mu, Changkao; Su, Qiong (Frontiers in Marine Science, 2022)
Scylla paramamosain is a high-quality cultivar for saline-alkaline water aquaculture as a euryhaline crustacean species. However, salinity impacts the respiratory metabolism, growth, and survival of marine crustaceans. The metabolic response of crabs adapting to multiple low salinity environments has not been thoroughly studied yet, especially in inland saline-alkaline water. In this study, we analyzed metabolites in the gill and hemolymph of crabs cultured in three different low salinity environments. The results showed that membrane composition (lipids and lipid molecules) and free amino acids played an essential role in the osmoregulation of crabs, and the energy consumption accompanied as well. Meanwhile, S. paramamosain relied on ion transport and energy metabolism under acute/short-term low salinity conditions for osmoregulation. In contrast, amino acids and energy metabolism occupied a leading position in long-term low salinity. Furthermore, taurine and hypotaurine play a vital role in crabs adapting to inland saline-alkaline water. This is the first study to identify the crucial metabolites and key pathways as biomarkers to differentiate the metabolic mechanisms of S. paramamosain in multiple low salinity stress modes based on GC-MS technology, which provided novel insight into the metabolic response of S. paramamosain adapting to inland low salinity saline-alkaline water, and provided theoretical guidance for the aquaculture of S. paramamosain in the inland saline-alkaline water.